Analisis Pasal 284 KUHP tentang Tindak Pidana Zina - M. Aunul Hakim (el Harakah: Jurnal Budaya Islam, 2006)
Indonesia is a state with a Criminal Code named KUHP. The regulation draft about adultery is especially mentioned at paragraph 284. According to this paragraph, the definition of adultery is sexual intercourse conducted by a man/woman who has valid marriage with another woman/man who is not his/her wife/husband and it is conducted based on the wish of each of them. In Criminal Code, it is stated that such deed may be imposed as a crime if there is a plea from the wife/husband who is harmed. Adultery crime is called as offense that warrants complaint, and punishment is nine months. It is different from the meaning of adultery according to Islamic Law which has meaning a sexual intercourse conducted by a man and woman who are not a valid pair of marriage. Besides, the criminal code was established based on rationale consideration. While the objective of legal realism is to construct the law which is more responsive toward the social need. Therefore KUHP regulation on adultery should be revisited to accomodate the Islamic values held by moslem as the dominant citizen in Indonesia.     Indonesia adalah negara dengan KUHP yang bernama KUHP. Rancangan peraturan tentang perzinahan terutama disebutkan pada paragraf 284. Menurut paragraf ini, definisi perzinahan adalah hubungan seksual yang dilakukan oleh seorang pria / wanita yang memiliki pernikahan yang sah dengan wanita / pria lain yang bukan isteri / suami dan istrinya. dilakukan berdasarkan keinginan masing-masing. Dalam KUHP, dinyatakan bahwa akta tersebut dapat dikenakan sebagai tindak pidana jika ada permintaan dari istri / suami yang dirugikan. Kejahatan perzinahan disebut sebagai pelanggaran yang menjamin pengaduan, dan hukuman sembilan bulan. Hal ini berbeda dengan makna perzinahan menurut Hukum Islam yang memiliki arti hubungan seksual yang dilakukan oleh pria dan wanita yang bukan pasangan perkawinan yang sah. Selain itu, kode pidana didirikan berdasarkan pertimbangan rasional. Sedangkan tujuan realisme hukum adalah membangun undang-undang yang lebih responsif terhadap kebutuhan sosial. Oleh karena itu peraturan KUHP tentang perzinahan harus ditinjau kembali untuk mengakomodasi nilai-nilai Islam yang dimiliki umat Islam sebagai warga negara yang dominan di Indonesia.